2000
DOI: 10.1046/j.1365-2672.2000.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year epidemiological study of extended-spectrum betabeta-lactamase-producing Klebsiella pneumoniae isolates in a medium- and long-stay neurological unit

Abstract: Thirty‐eight different strains of extended‐spectrum β‐lactamase (ESBL)‐producing Klebsiella pneumoniae (ESBL Kp), isolated from urine and pus samples of 38 patients hospitalized in a medium‐ and long‐stay neurology department between 1 January 1992 and 31 December 1996, were analysed by antibiotic resistance phenotyping, DNA macrorestriction by pulsed‐field electrophoresis and isoelectric focusing of β‐lactamases. An epidemiological survey was conducted to identify risk factors for infection by ESBL Kp in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
0
15
0
2
Order By: Relevance
“…This diversity in genotype was also described in Taiwan by Liu et al (30) who suggested that the increase of ESBL K. pneumoniae in their hospital was mainly due to dissemination, or mutation, in plasmids containing resistant genes. Conversely, in other centers the increase of ESBL K. pneumoniae was correlated with a single, or few, clones (17,30).…”
Section: Discussionmentioning
confidence: 79%
“…This diversity in genotype was also described in Taiwan by Liu et al (30) who suggested that the increase of ESBL K. pneumoniae in their hospital was mainly due to dissemination, or mutation, in plasmids containing resistant genes. Conversely, in other centers the increase of ESBL K. pneumoniae was correlated with a single, or few, clones (17,30).…”
Section: Discussionmentioning
confidence: 79%
“…Pulsed-field gel electrophoresis of chromosomal DNA is probably the most widely used method of genotyping ESBL-producing organisms (15,17,57,68,85,113,128,132,149,207,218,222,234,235,256,268,298,328,334,341,348,351,358,374,381,408,426,431,439). These references describe the restriction enzymes used for various organisms harboring ESBLs.…”
Section: Use Of Typing Methodsmentioning
confidence: 99%
“…Numerous studies have used a case-control design with which to assess risk factors for colonization and infection with ESBL-producing organisms (16,19,40,96,103,205,222,234,291,299,311,358,419). Analysis of the results of these studies yelds a plethora of conflicting results, likely due to the differences in study populations, selection of cases, selection of controls, and sample size (286).…”
Section: Risk Factors For Colonization and Infection With Esbl Producersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results are conflicting due to study populations, geographical areas, selection of cases and controls and sample size. (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Despite these statistical differences, some generalizations can be made.…”
Section: Risk Factors For Colonization /Infection With Esblmentioning
confidence: 99%